Corporate Criminal Liability of Corruption Criminal Actions PT. Sinarmas Asset Management: Study of Supreme Court Ruling Number 1228 K/Pid.Sus/2023 - Indraswara, Dede; Masyhar Mursyid, Ali; Wulandari, Cahya (Universitas Negeri Semarang, 2024)
Corporations, as legal entities, can be held criminally liable for corruption offenses under Indonesian law. The legal framework in Indonesia recognizes corporations as subjects of criminal law, as outlined in Law No. 20 of 2001 concerning the Eradication of Corruption Crimes (UU Tipikor). However, there are still gaps in the law, particularly regarding main and additional penalties for corporate entities. The introduction of Law No. 1 of 2023 concerning the Criminal Code (KUHP Nusantara) addresses these shortcomings by providing more comprehensive regulations on corporate criminal liability, particularly for corruption-related offenses. This study employs a qualitative research approach, using legislative analysis, case law examination, and conceptual analysis. The research is doctrinal and juridical-normative, relying on literature studies and document analysis of statutory regulations and court decisions regarding corporate corruption. The study focuses on the corruption case involving PT. Sinarmas Asset Management (PT. SAM), where the corporation was held criminally liable under both the Anti-Corruption Law and the Indonesian Criminal Code. The research reveals that the Indonesian Criminal Code offers more detailed provisions, including additional penalties for corporations convicted of corruption. The case study also highlights significant legal developments in the trial process. Initially, the District Court convicted PT. SAM of corruption, but this verdict was overturned by the Jakarta High Court, which acquitted the company. However, the Supreme Court disagreed with the lower courts and upheld the conviction, continuing to impose penalties on PT. SAM for the mismanagement of unauthorized funds. This case underscores the complexities of corporate criminal liability in corruption cases and the evolving nature of judicial interpretations of corporate accountability in Indonesia.